Onosma sanninensis (Boraginaceae), a new species from the Mount Sannine Central Lebanon - Maalouf, Ramy; Binzet, Riza (Phytotaxa, 2025)
In this study, a new species of Onosma (Boraginaceae: Lithospermeae), subsect. Asterotricha, from Mount Sannine, Lebanon, is described and illustrated. This new species was conclusively identified through a comprehensive analysis of morphological features and geographical distributions compared across herbarium specimens from multiple collections. The new species is closely related to O. caerulescens and O. inexspectata, but it is different with 1–2 terminal cymes, smaller bracts, longer pedicels in fruit, larger calyx in flower and fruit, different corolla color, smaller anthers, and different pollen shape. Additionally, geographical distributions and map, an image of the holotype specimen, diagnostic characters, detailed photographs, habitat descriptions, and an identification key for the new species, O. caerulescens, and O. inexspectata are provided, along with a vernacular name and IUCN conservation status.